Radio Frequency Numerical Simulation Techniques Based on Multirate Runge-Kutta Schemes - Jorge F. Oliveira; José C. Pedro (Journal of Applied Mathematics)
Electronic circuit simulation, especially for radio frequency (RF) and microwave telecommunications, is being challenged by increasingly complex applications presenting signals of very different nature and evolving on widely separated time scales. In this paper, we will briefly review some recently developed ways to address these challenges, by describing some advanced numerical simulation techniques based on multirate Runge-Kutta schemes, which operate in the one-dimensional time and also within multidimensional frameworks.